Prevalence of undiagnosed hypertension and associated factors among adults in Durame town, Southern Ethiopia: a cross-sectional study - Suliman, Abebe; Tadesse, Sebsibe; Abute, Lonsako; Selamu, Markos (Frontiers in Epidemiology, 2023)
Background Undiagnosed hypertension is a major public health problem causing severe cardiovascular disorders that are responsible for a high proportion of morbidities and mortalities, especially among adults living in low-income countries. However, there is a paucity of information that describes its epidemiology in Ethiopia. This study aimed to assess the prevalence of undiagnosed hypertension and associated factors among adults in Durame town, southern Ethiopia. Methods A community-based cross-sectional study was conducted from July to September 2022. Data were collected from 526 randomly selected adults aged ≥18 years using a pre-tested questionnaire. The binary logistic regression models were used to identify factors associated with undiagnosed hypertension. Results The prevalence of undiagnosed hypertension among adults in Durame town, southern Ethiopia, was found to be 14.0% (95% CI: 11.2–17.1). Family history of hypertension [AOR = 6.9, 95% CI: (3.62, 13.27)], drinking too much alcohol [AOR = 5.7, 95% CI: (2.97, 10.75)], physical inactivity [AOR = 2.5, 95% CI: (1.34, 4.73)], consuming street foods regularly [AOR = 2.8, 95% CI: (1.28, 6.01)], and seeking healthcare for hypertensive symptoms without serious illness [AOR = 2.4, 95% CI: (1.28, 4.56)] were significantly associated with developing undiagnosed hypertension. Conclusion The study has revealed that one in seven adults had undiagnosed hypertension in the study area. Thus, interventions to prevent hypertension should target increasing awareness among people with a family history of hypertension, controlling excessive alcohol consumption, promoting physical exercise, regulating street food markets, and improving the health-seeking behavior of adults in urban settings.